The Relationship Between Lecturers’ Communication Styles and Student Loyalty in the Context of Higher Education Marketing Communication - Putri Maulana, Shafira Alisya; Rahmawati, Reni; Kurnia, Yosi; Zaqia, Afrinur; Weriframayeni, Annisa (Edumaspul: Jurnal Pendidikan, 2025)
academically but also build long-term relationships with students. One strategic factor contributing to this relationship is the communication style of lecturers, the primary actors in academic interactions. This study aims to analyze the relationship between lecturer communication style and student loyalty in the context of higher education marketing communications. The study employed a quantitative approach with a survey method involving active students of the Faculty of Economics, Business, and Social Sciences, Perintis Indonesia University, class of 2023. The study population consisted of 50 students, with 30 actual respondents who completed a complete and valid questionnaire. The research instrument was a five-point Likert scale questionnaire measuring lecturer communication style and student loyalty. Data analysis was conducted using Pearson correlation and simple linear regression. The results showed a positive and significant relationship between lecturer communication style and student loyalty (r = 0.681; p < 0.05). Lecturer communication style contributed 46.4% to student loyalty. These findings confirm that lecturer communication is a crucial part of a higher education institution’s internal marketing strategy in building student loyalty.